Efektivitas Ekstrak Kulit Salak Pondoh Berbagai Konsentrasi dalam Menghambat Bakteri Penyebab Periodontitis (Kajian In Vitro) - Aprilia Yuanita Anwaristi (Universitas Respati Indonesia, 2025)
Salacca zalacca or popular with name salak contains various bioactive compounds, including flavonoids, tannins, saponins, and alkaloids, which exhibit antibacterial properties. This study investigates the inhibitory effect of Pondoh salak peel extract on the growth of Porphyromonas gingivalis, a major pathogen implicated in periodontitis. The research aims to determine the optimal concentration of the extract for maximum bacterial inhibition. Using a post-test only control group experimental design, the antibacterial activity was assessed through the paper disc diffusion method. Treatment groups were administered Pondoh salak peel extract at concentrations of 25%, 30%, 35%, and 40%, while chlorhexidine gluconate 0.2% served as a positive control and distilled water as a negative control. Each paper disc was saturated with 30 µL of extract or control solution. Data analysis was performed using One-Way ANOVA to compare inhibition zones among the groups. Results from the One-Way ANOVA indicated a revealing statistically significant differences in inhibition zones across the various extract concentrations. Additionally, the Post Hoc Least Significant Difference (LSD) test also confirming significant variation in antibacterial effects between the extract concentrations. The 35% extract concentration produced the largest inhibition zone, indicating the most potent antibacterial effect against Porphyromonas gingivalis. This study concludes that Pondoh salak peel extract significantly inhibits the growth of Porphyromonas gingivalis, with the 35% concentration being the most effective. These findings suggest that Salacca zalacca extract holds potential as a natural antibacterial agent for managing periodontitis.